Correlation between arachidonic acid metabolites and vascular endothelial dysfunction in Chinese elderly with type 2 diabetes mellitus - Yali Huang; Tong Lu (Cardiology Plus, 2016)
Objective: This study was carried out to determine the correlation between arachidonic acid metabolites and vascular endothelial dysfunction in older Chinese patients diagnosed with type 2 diabetes mellitus. Methods: High-resolution ultrasound was employed to measure flow-mediated dilation (FMD) and sublingual nitroglycerin-induced dilation (NID) of the brachial artery. Serum 14,15-dihydroxyeicosatrienoic acid (14,15-DHET), the end-product of 14,15-epoxyeicosatrienoic acid (14,15-EET) and 6-keto-prostaglandin F1α (6-keto-PGF1α), and the end-product of prostacyclin (PGI2) were measured in 60 healthy elderly volunteers, 78 senile diabetic (SD) patients without nephropathy (SD), and 58 SD patients with nephropathy (SDN). Results: Compared to healthy elderly volunteers, serum 14,15-DHET and 6-keto-PGF1α levels were reduced by 50% in SD. No further reduction was observed in SDN. 6-keto-PGF1α was associated with FMD, but not with NID in the brachial artery of healthy elderly volunteers. Brachial FMD and NID in were impaired in all diabetic patients. The correlation between FMD and 6-keto-PGF1α or 14,15-DHET was lost in diabetic patients. On the other hand, NID was positively correlated with 6-keto-PGF1α or 14,15-DHET in SD. Only NID and 6-keto-PGF1α correlation persisted in SDN. In addition, brachial artery dysfunction was negatively correlated with urinary albumin excretion and serum triglyceride in SDN patients. Conclusions: Impaired brachial artery vasodilation was associated with reduced PGI2and EET production in older Chinese subjects with type 2 diabetes.